2005
DOI: 10.1111/j.1365-2222.2005.02405.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of pulverized Konjac glucomannan prevents the increase of plasma immunoglobulin E and immunoglobulin G levels induced by the injection of syngeneic keratinocyte extracts in BALB/c mice

Abstract: These results suggested that oral administration of PKGM prevents the elevation of plasma IgE by suppressing IgE class switching in B cells and/or the commitment development of naive lymphocytes to both T-helper type 1 (Th1) and Th2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 37 publications
0
28
1
Order By: Relevance
“…This result differs from our previous data, which indicated that dietary PKGM suppressed both total IgE and IgG1 levels in NC/Nga mice 4,6) and in BALB/c mice upon injection with syngeneic keratinocyte extract. 7) This discrepancy in the data might be due to differences in experimental settings (e.g., mouse strain, immunization protocols).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result differs from our previous data, which indicated that dietary PKGM suppressed both total IgE and IgG1 levels in NC/Nga mice 4,6) and in BALB/c mice upon injection with syngeneic keratinocyte extract. 7) This discrepancy in the data might be due to differences in experimental settings (e.g., mouse strain, immunization protocols).…”
Section: Discussionmentioning
confidence: 99%
“…7) Briefly, 96-well microtiter plates were coated with OVA solution (100 mg/ml) at 4 C overnight, and then incubated with diluted plasma samples ( 10 for IgE, and  500 for IgG1 and IgG2a). After reaction with secondary biotinylated rat anti-mouse IgE, IgG1, or IgG2a antibody (BD Bioscience, San Jose, CA, 1:250 dilution) and subsequent incubation with streptavidin-conjugated alkaline phosphatase (Zymed Laboratories, San Francisco, CA, 1:1,000 dilution), enzyme reaction was performed using the AttoPhos Ò substrate system (Promega Corporation, Madison, MI).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the compound suppressed both Th1 and Th2 related cytokines it's mechanism of action cannot be attributed to Th1/Th2 polarization (Onishi et al, 2004(Onishi et al, , 2005. Follow up studies found that it decreased scratching behvaiour in a dose dependent manner (OnishiKawamotoSuzuki et al, 2007), and prevented IgE class switching in Balb/c mice following injection of keratinocyte extract (Oomizu et al, 2006). It was also found to suppress allergic rhinitis like inflammation following nasal challenge with ovalabumin (OnishiKawamotoUeda et al, 2007).…”
Section: Konjac Glucomannanmentioning
confidence: 96%
“…Furthermore, PGE2 production activates Th2 cells to secrete inflammatory cytokines, such as IL-5, which stimulate B-cells to induce IgE. It is recognized that high levels of IgE are one of the charac-teristics of AD, and clinical observations suggest a correlation between serum IgE levels and the extent of disease (18)(19)(20). Therefore, we assessed changes in COX-2 and IgE levels associated with the symptomatic cycle of AD in this study.…”
Section: Discussionmentioning
confidence: 99%